Practitioner's guide to symptom baserRates in thegGeneral population - McCaffrey, Robert J. (Springer New York, 2006)
A Brief overview of base rates -- Control groups: adult control groups -- College students -- Combat veterans -- Community members -- Family practice -- General practice patients -- Internal medicine -- Litigants -- Medical and dental students -- Neurology -- Nonsmokers -- Normal -- Occupational -- Psychiatric adults -- Child and adolescent control groups -- Clinic referred children -- Delinquents -- Elementary school children -- High school students -- Psychiatric referred children -- Secondary school students -- Special education students -- Elderly control groups -- Alzheimer’s disease spouses -- Frail elderly -- Nursing home -- References -- Symptom Index.